2016
DOI: 10.4103/0970-0218.177529
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dots treatment default among new HIV-TB coinfected patients in Nalgonda (Dist.) Telangana (State): A case control study

Abstract: Background:The therapeutic regimens as recommended by the Revised National TB Control Programme (RNTCP) have been shown to be highly effective for both preventing and treating tuberculosis, but poor adherence to medication is a major barrier to its global control.Aim and Objectives:The study was conducted to assess the influence of patient related factors for DOTS Treatment Default among HIV-TB Co-infected cases.Setting and Design:This was a case control study conducted in Nalgond, Telangana.Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Patients who ran their businesses were also significantly more likely to enrol in CBDOT compared to FBDOT. This finding was supported by studies in Ethiopia [14] and India [15] . A possible explanation could be that these patients are always engaged with their daily work thus, CBDOT is convenient for them.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Patients who ran their businesses were also significantly more likely to enrol in CBDOT compared to FBDOT. This finding was supported by studies in Ethiopia [14] and India [15] . A possible explanation could be that these patients are always engaged with their daily work thus, CBDOT is convenient for them.…”
Section: Discussionsupporting
confidence: 73%
“…Across all spectrums of employment, patients were likely to be cured compared to the unemployed. This finding was supported by studies in Ethiopia [14] and India [15] indicating a lower likelihood of having successful TB outcomes among the unemployed and unskilled occupations than among the employed. This could be explained that the employed has a reliable socioeconomic status, which may influence treatment outcomes through its impact on improved nutrition, and thereby is associated with the increased strength of the immune system and improved clinical outcomes [28] , [29] .…”
Section: Discussionmentioning
confidence: 52%
“…A recent study conducted in the same scenario showed that the need for hospitalization for TB treatment is more frequent in non-white patients living in poverty [34]. In our study, schooling was used as a proxy for the economic situation, and, although schooling was not associated with DOT, the lower the schooling, the greater the percentage of DOT, a trend already observed in other studies [33,35].…”
Section: Discussionsupporting
confidence: 60%
“…Notwithstanding, the district has a health center that is historically considered one of the pioneers in tuberculosis treatment [18]. Sex and age were not associated with the outcome, as in other studies that point out that these are not decisive factors for the performance of DOT [3133]. In terms of sociodemographic variables, data on race and schooling show the vulnerability associated with DOT.…”
Section: Discussionmentioning
confidence: 88%
“…Thirty-nine studies were accounted for pooled prevalence analysis, which included 32 020 treatment interrupters out of 654 872 populations in the study cohorts. All case–control studies and one cross-sectional study were excluded due to a fixed ratio sampling between treatment interrupters and non-interrupters,17–26 while another cross-sectional study included all interrupters in the study population 27. The overall pooled estimated prevalence for the Asia region was 17% (95% CI 16% to 18%).…”
Section: Resultsmentioning
confidence: 99%